The differential association between local neurotransmitter levels and whole‐brain resting‐state functional connectivity in two distinct cingulate cortex subregions. Issue 9 (1st March 2022) - Li, Meng; Danyeli, Lena Vera; Colic, Lejla; Wagner, Gerd; Smesny, Stefan; Chand, Tara; Di, Xin; Biswal, Bharat B.; Kaufmann, Jörn; Reichenbach, Jürgen R.; Speck, Oliver; Walter, Martin; et al.
Abstract : We examined the association between rsFC and local neurotransmitter levels in the pregenual anterior cingulate cortex (pgACC) and the anterior mid‐cingulate cortex (aMCC) by varying rsFC‐strengths at the whole‐brain level. Our results showed region‐dependent directionality of associations in the investigated ACC subdivisions. Abstract: Reproducible resting‐state functional connectivity (rsFC) patterns and their alterations play an increasing role in neuropsychiatric research. Studies that limit the analysis of metabolites and rsFC strengths to a predefined canonical network suggest that the rsFC strength positively correlates with the local glutamate (Glu) levels and negatively correlates with the gamma‐aminobutyric acid (GABA) levels. The contribution of regional neurotransmitter activity to rsFC strengths from a given seed to the whole‐brain remains unclear. In this study, 121 healthy participants (50 female/71 male) underwent multimodal resting‐state functional magnetic resonance imaging (rsfMRI) and magnetic resonance spectroscopy (MRS) at 7 T, allowing for acquisition of multiple, neuroanatomically well‐defined MRS voxels in the same session. We examined the association between rsFC and local neurotransmitter levels in the pregenual anterior cingulate cortex (pgACC) and the anterior mid‐cingulate cortex (aMCC) by varying rsFC strengths at the whole‐brain level. Our results showed that both glutamatergic and GABAergic edge weights (defined as the across‐participants partial correlation coefficients between the local metabolite levels and the rsFC of the seed region to each target parcel) were positively correlated with the rsFC strengths in the pgACC and negatively correlated with the rsFC strengths in the aMCC. The region‐dependent directionality of associations may indicate that region‐specific microscale properties, such as neurotransmitter receptor architecture, modulate the interaction between brain regions at the macroscale level.